Research on Optical Spectrum Processing for Photonic-Assisted Broadband RF Cross- Eye Jamming System - Yunlu Xing; Shangyuan Li; Xiaoxiao Xue; Xiaoping Zheng (IEEE Photonics Journal, 2023)
Cross-eye jamming technology has been used in electronic warfare, which attempts to protect a military platform from monopulse tracking radars. The cross-eye jamming technology has the ability of inducing angular errors to the monopulse tracking radars by transmitting two jamming signals with equal amplitudes and opposite phases. At present, high operation frequency and broadband cross-eye jamming system has been rarely demonstrated. Therefore, the present cross-eye jamming systems are hard to jam frequency-agile radar or multi-band radar, whose carrier frequency covers a large spectral range. In this paper, a photonic-assisted broadband radio frequency (RF) cross-eye jamming system is proposed and experimentally demonstrated. To achieve effective jamming effect, the intercepted radar signal is modulated to optical carriers and the phase shift is realized by optical spectrum processing. The relationship between system parameter tolerances and jamming effects are also simulated. Furthermore, the RF transfer function of X-band, Ku-band and K-band has been obtained in the experiments. The experimental results show that the amplitude and phase mismatch are below 2.15 degrees and 0.4 dB, respectively. Calculated cross-eye gain is 39 dB.